Pengaruh Copywriting Dan Desain Kemasan Minuman Oatside Dalam Membentuk Brand Awareness Produk Minuman Kemasan Oatside - Ardita, Yasmin Elysia (Innovative: Journal Of Social Science Research, 2025)
This study aims to examine the influence of packaging design and copywriting on the development of brand awareness for the Oatside beverage product. Within a highly competitive market saturated with visual and verbal marketing strategies, Oatside stands out through its distinctive packaging design and witty, communicative copywriting. The research adopts a quantitative explanatory survey method involving 113 respondents aged ≥ 17 years who have seen or consumed Oatside. Data were collected through online and offline questionnaires and analyzed using validity tests, reliability tests, Pearson correlation, multiple regression, and cross-tabulation via SPSS software. The findings indicate that both packaging design and copywriting significantly influence brand awareness, with copywriting being the more dominant variable. The correlation test also reveals a strong positive relationship between the two independent variables, highlighting the importance of consistent visual and verbal messaging. Additionally, the 21–30 year age group emerges as the most exposed and brand-aware segment. The implications underscore the strategic role of integrating visual and narrative elements in packaging as an effective brand communication tool to build strong brand equity.